2017
DOI: 10.23925/2176-901x.2017v20i2p247-269
|View full text |Cite
|
Sign up to set email alerts
|

Atenção à saúde da pessoa idosa e ao envelhecimento em uma rede de serviços de Atenção Primária.

Abstract: O objetivo deste estudo foi analisar os serviços de Atenção Primária à Saúde quanto à oferta e organização de ações ao envelhecimento e à saúde da pessoa idosa, de uma Rede Regional de Atenção à Saúde do centro-oeste paulista. Foram utilizados indicadores do Questionário de Avaliação da Qualidade de Serviços de Aten­ção Básica (QualiAB) de 2014. Os resultados sugerem que estes serviços desenvolvem ações de atenção ao envelhecimento de modo incipiente e limitado às doenças crônicas não transmissíveis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
9

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 12 publications
0
3
0
9
Order By: Relevance
“…This is corroborated by a descriptive study previously conducted by the authors with analysis of the response frequencies of these primary care services on the indicators. This study identified: the presence of a support group for older adults' caregivers in few services (8.2%), the use of a protocol to attend cases of violence against older adults (12.1%), a record with differentiated risk for people with chronic conditions (31.2%), and inclusion of older adults' health as the subject of continuing education for the professional team (33.1%) 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is corroborated by a descriptive study previously conducted by the authors with analysis of the response frequencies of these primary care services on the indicators. This study identified: the presence of a support group for older adults' caregivers in few services (8.2%), the use of a protocol to attend cases of violence against older adults (12.1%), a record with differentiated risk for people with chronic conditions (31.2%), and inclusion of older adults' health as the subject of continuing education for the professional team (33.1%) 11 .…”
Section: Discussionmentioning
confidence: 99%
“…National and international studies conducted to evaluate the older adults' care in PHC indicate the need to expand preventive practices and health promotion, infrequent and low diverse in actions, in addition to the importance to build networks of comprehensive care to older adults' health, ordained by PHC services [5][6][7][8][9][10] . The QualiAB 2014 instrument (Questionnaire for Primary Care Services Assessment and Monitoring) proposes, among its indicators for the comprehensive evaluation of primary care services, those directed to older adults' care 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Sobre a integralidade, onze estudos (Placideli, 2018;Leandro, 2017;Filho, 2016;Silva, 2016;Macedo, 2016;Arantes, 2016;Coutinho, 2016;Monti, 2016;Miclos, 2015;Nasser, 2015;Lindemann, 2015) destacaram a atenção à saúde, com enfoque na integralidade da saúde em realidades distintas. Foram encontrados estudos compreendendo as ações de promoção, prevenção e garantia de atendimento em todos os níveis de atenção (Placideli, 2018;Leandro, 2017;Filho, 2016;Macedo, 2016;Monti, 2016;Miclos, 2015;Lindemann, 2015). Estudo (Souza, 2016) apontou o Núcleo de Apoio à Saúde da Família -NASF como potencializador no escopo de ações na AB, embora suas ações predominantes perpassem a dimensão técnico assistencial.…”
Section: Integralidadeunclassified
“…O instrumento foi desenvolvido em 2007 (22, 25) e atualizado em 2014 e 2016 (www.abasica.fmb.unesp.br). Tem resultados analisados segundo diferentes recortes (26, 27). A versão de 2014 era composta por 126 questões de múltipla escolha que geravam indicadores de assistência e de gerência.…”
Section: Materiais E Métodosunclassified